Comparison of patients with axial PsA and patients with axSpA and concomitant psoriasis: an analysis of the German register RABBIT-SpA. Issue 1 (10th March 2023) - Regierer, Anne Constanze; Weiß, Anja; Proft, Fabian; Baraliakos, Xenofon; Behrens, Frank; Poddubnyy, Denis; Schett, Georg; Lorenz, Hanns-Martin; Worsch, Matthias; Strangfeld, Anja
Abstract : Background: Psoriatic arthritis (PsA) and axial spondyloarthritis (axSpA) show certain overlaps: A subset of patients with PsA can develop axial involvement (axial PsA, axPsA), while a subset of patients with axSpA presents with psoriasis (axSpA+pso). Treatment strategy for axPsA is mostly based on axSpA evidence. Objectives: To compare demographic and disease-specific parameters of axPsA and axSpA+pso. Methods: RABBIT-SpA is a prospective longitudinal cohort study. AxPsA was defined based on (1) clinical judgement by rheumatologists; (2) imaging (sacroiliitis according to modified New York criteria in radiographs or signs of active inflammation in MRI or syndesmophytes/ankylosis in radiographs or signs of active inflammation in spine MRI). axSpA was stratified into axSpA+pso and axSpA without pso. Results: Psoriasis was documented in 181/1428 axSpA patients (13%). Of 1395 PsA patients, 359 (26%) showed axial involvement. 297 patients (21%) fulfilled the clinical definition and 196 (14%) the imaging definition of axial manifestation of PsA. AxSpA+pso differed from axPsA regardless whether clinical or imaging definition was used. axPsA patients were older, more often female and less often HLA-B27+. Peripheral manifestations were more often present in axPsA than in axSpA+pso, whereas uveitis and inflammatory bowel disease were more common in axSpA+pso. Burden of disease (patient global, pain, physician global) was similar among axPsA and axSpA+pso patients. Conclusions: AxPsA differs from axSpA+pso in its clinical manifestations, irrespective of whether axPsA is defined clinically or by imaging. These findings support the hypothesis that axSpA and PsA with axial involvement are distinct entities, so extrapolation of treatment data from randomised controlled trials in axSpA should be performed with caution.